(untitled) (Bangladesh Journal of Nuclear Agriculture, 2023)
This study was carried out during May 2021 to January 2022 at the Tissue Culture Laboratory of Biotechnology Division, Bangladesh Institute of Nuclear Agriculture (BINA), Mymensingh, Bangladesh for callus induction and regeneration ability of plantlet from low doses irradiated embryogenic calli of Binadhan-13 and BR5 (Dulabhog). The effect of low gamma rays such as 4, 6 and 8 Gy were observed in vitro shoot, root and plantlet formation. Two different incubation conditions such as light and dark incubation were maintained. Between two varieties, Binadhan-13 showed the highest ability of callus induction in both conditions. Callus induction was significantly higher under dark condition (77.14%) than light condition (67.14%) ‍at 21 days. Data revealed that gamma rays affect both shoot and root regeneration ability of embryogenic callus. Shoot regeneration ability was the highest at 4 Gy in Binadhan-13 (60%) and gradually decreased with the increased doses of gamma rays. Among the treatments, shoot regeneration ability (60% in Binadhan-13 and 50% in BR5) was higher at 4 Gy dose of gamma ray followed by 6 Gy where shoot regeneration ability was 55% and 45% in Binadhan-13 and BR5 respectively. In root induction, the highest root induction ability (80%) was observed in the cultivar Binadhan-13 at control condition. Like shoot regeneration, 4 Gy gamma ray showed better root induction in both the varieties (70% in Binadhan-13, 60% in BR5). The in vitro regenerated plantlets from irradiated embryogenic calli were successfully transferred to soil in pots. The regeneration protocol could be further used for varietal improvement of rice varieties using nuclear technique (60Co gamma ray). Bangladesh J. Nuclear Agric, 37(2): 29-42, 2023